Assessing the nurse's knowledge and opinions regarding the management of persons with physical disabilities in two healthcare settings in Kimberley - Snyman, Johanna Hendrina (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MCur)- -University of Stellenbosch, 2011